Análise econômica das opções de biometanização, compostagem e reciclagem para tratamento de resíduos sólidos urbanos no Brasil - Carvalho, Matheus Vieira (2021)
This Master's Dissertation proposed to economically analyse the biomethanization and composting options for the treatment of putrescible Municipal Solid Waste (MSW) generated throughout Brazil and the option of recycling to reuse other MSW produced in our national territory. For the development of this academic work, firstly ABRELPE data about MSW in Brazil was obtained, then future projections of the parameters associated to MSW have done by the linear regression method. Soon after, an average value of interest rates and inflation was estimated for future years in our country, in addition to finding an average gravimetric composition of the MSW produced in Brazil. In the methodology, it was still sought to calculate the estimators of the MSW treatment processes per ton of waste, using again the linear regression method, to use them during the economic analysis procedure, which were performed for the scenarios of 5, 10, 15 and 20 years of project lifetime. As a result, it was concluded that the putrescible MSW treatment processes by biomethanization are more economically viable than composting. For recycling, this Master's Dissertation pointed out that, for the project lifetimes of 5 and 10 years, the MSW of the subcategories of 'Rigid / Hard Plastic', 'Malleable / Flexible Plastic', 'Paper' and 'Aluminium' are economically viable for exploitation, already for 15 and 20 years of project lifetimes, there is the inclusion of the subcategory 'Board' in the list of MSW with economic viability for recycling.